Academic Procrastination in Language Learning: Adolescent Learners’ Perspectives - Asmalı, Mehmet; Dilbaz Sayın, Sanem (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
Despite the abundance of studies investigating the impact of academic procrastination on several aspects of learning, less is known about how this construct is perceived by adolescent foreign language learners with different levels of academic procrastination and their reasons to delay tasks and potential suggestions to reduce it. This study was designed to find out the academic procrastination behaviors of 136 learners aged 11-12. Additionally, another major aim was to find out how the participants’ reasons to procrastinate and suggestions to reduce it differed according to gender and their academic procrastination level. The participants were divided into three groups as low, average, and high procrastinators considering their mean scores on academic procrastination scale. A focus group interview was conducted with 12 learners to create a list of reasons, replacement activities, and suggestions. The findings indicated that all three groups followed a similar academic procrastination behavior pattern. However, in terms of reasons, while boys preferred playing computer games as a replacing activity, girls were more inclined to read books. Some suggestions were also provided by the learners to reduce it. The study provides implications for teachers, parents, and learners.